Sponge city and its compensatory techniques: a systematic literature review (Research, Society and Development, 2022)
The objective of this study is to analyze published studies with the theme of sustainable water management through the elaboration of a Systematic Literature Review (SLR), focusing on the recently created concepts of Sponge City (SC) and Water Sensitive City (WSC) by gathering information on how these concepts positively contribute to the sustainable urban development of cities. In addition, it sought to highlight the advantages and challenges observed during the planning and/or implementation of these concepts. Of the 25 articles analyzed, 19 were developed in China.  The biggest challenge found was the lack of a team with multidisciplinary experience for the development of urban planning, while the biggest advantage was the flood resilience acquired by cities. It was concluded that this topic has already been matured in several locations, a good technical knowledge about different devices has already been developed, and it is practical and feasible to apply the concepts of SC and WSC in different regions across many countries.